Analysis of Product Sales on Credit at NR Beauty Care in Lemahabang Sub-District - Agustin, Karmila; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
This research is a study on the Analysis of Product Sales on Credit at NR Beauty Care in Lemahabang District. This study aims to determine how product sales on credit at NR Beauty Care and analyze how product sales on credit can increase revenue. The method used in this research is qualitative. The results of this study indicate that product sales on credit are given to NR Beauty Care customers who have joined for at least 3 months. The credit facility given to customers still refers to the terms of credit sales that apply at NR Beauty Care by checking in advance about the character of the customer, the activeness of the customer in buying products at NR Beauty Care, and customers who are loyal to NR Beauty Care. NR Beauty Care takes a profit of 2-3% from each product. Based on the results and discussion that has been stated in this article that credit sales aim to help customers, especially reseller customers, to develop their business. If credit is channeled for business development or opening a new business, it will increase their income as well as reduce unemployment. The difference in revenue from credit and cash sales each month reaches Rp. 82,127,000, so selling products on credit at NR Beauty Care is effective for increasing revenue. The results of this study are used as input for NR Beauty Care owners in selling products on credit appropriately, making commitments with customers to avoid late payments and creating good relationships with customers. In addition, to increase revenue NR Beauty Care owners can utilize other E-commerce promotional media.